INVENTAIRE DE LA FAUNE ACRIDIENNE DANS DEUX BIOTOPES DE L’EST ALGERIEN (Sciences & Technologie. C, Biotechnologies, 2007)
The bio-systematic study of Grasshopper species assessed in two different biotopes in the East of Algeria : the region of Biskra (saharian zone) and the area of Constantine (semi-aride zone) permitted us to assess thirty one species. The later were distributedinto four families (Acrydiidae, Pamphagidae, Pyrgomorphidae and Acrididae). The last family was well represented comparing to other nine subfamilies which totalized twenty eight species in the study regions. These sub-families contained twenty three genuses. The great number of species was found in the sub-family of Oedipodinae with ten species divided in six genuses. The Grasshopper fauna assessment totalized twenty one species in the region of Biskra. Only sixteen species were assessed in the region of Constantine. Among these Grasshopper species, some have a wide geographic distribution and were found in the two biotopes. Other species are able to become dangerious for cultures.